2015
DOI: 10.1038/pr.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Early formation of bilirubin isomers during phototherapy for neonatal jaundice: effects of single vs. double fluorescent lamps vs. photodiodes

Abstract: Background:In neonatal jaundice, phototherapy converts bilirubin to more polar photoisomers which can be excreted without conjugation. We measured changes in the concentration of bilirubin Z,E-photoisomer during the first 4 h of intensive phototherapy using single fluorescent lights as a reference, compared to double fluorescent lights, and a single unit of photodiodes. Methods: Neonates (N = 42; birth weight: 1,200-4,690 g; gestational age: 28-42 wk) were studied during phototherapy. Infants were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
4
21
0
1
Order By: Relevance
“…After 24 h of phototherapy, the percentage of Z,E-bilirubin to total bilirubin isomers was higher for infants treated with light centered at 459 nm than for those treated with light centered at 497 nm (23% vs. 14%), and thus also the percentage of total bilirubin isomers formed during treatment to total bilirubin isomers was highest for the infants treated with light centered at 459 nm (26% vs. 18%) ( Table 3). This is in agreement with previous in vitro studies, which showed that after equilibrium between Z,Z-and Z,Eisomers is reached, the percentage of Z,E-bilirubin decreases with longer wavelengths (4,16).This observation has also been confirmed in earlier clinical studies, where the reported percentages of Z,E-bilirubin to total bilirubin isomers were: 24% to 27% (10,13,14), 16% (10) and 9% (14) in children exposed to light of wavelengths ~460, 490, and 528 nm, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After 24 h of phototherapy, the percentage of Z,E-bilirubin to total bilirubin isomers was higher for infants treated with light centered at 459 nm than for those treated with light centered at 497 nm (23% vs. 14%), and thus also the percentage of total bilirubin isomers formed during treatment to total bilirubin isomers was highest for the infants treated with light centered at 459 nm (26% vs. 18%) ( Table 3). This is in agreement with previous in vitro studies, which showed that after equilibrium between Z,Z-and Z,Eisomers is reached, the percentage of Z,E-bilirubin decreases with longer wavelengths (4,16).This observation has also been confirmed in earlier clinical studies, where the reported percentages of Z,E-bilirubin to total bilirubin isomers were: 24% to 27% (10,13,14), 16% (10) and 9% (14) in children exposed to light of wavelengths ~460, 490, and 528 nm, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of Z,E-bilirubin increases until equilibrium with Z,Z-bilirubin is reached, which occurs after approximately 4-6 h of exposure to light (13)(14)(15). Thereafter, the percentage of Z,E-bilirubin to the sum of Z,Z-and Z,E-bilirubin only depends on the emission spectrum of the light (15).…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, there is increasing, although indirect, evidence that isomerization of bilirubin in vivo primarily occurs in the skin capillary circulation (10,11). Our findings support this understanding.…”
Section: Discussionsupporting
confidence: 79%
“…However, it has also been shown that routinely alternating the infant's position during phototherapy does not increase the effect of phototherapy, presumably because it happens in the capillary circulation near the skin's surface . This was compatible with studies that showed that formation of bilirubin photoisomers was detectable within a few minutes of turning on phototherapy lights, long before diffusion from the skin tissue could have occurred .…”
Section: Discussionsupporting
confidence: 60%